Digitalisasi Tata Kelola Masjid At Taqwa Krandon Kudus Berbasis Website untuk Peningkatan Layanan dan Transparansi - Muhammad Sholikhan; Aftuqa Sholikatur Rohmania; Risma Nurhapsari (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service project aimed to address the lack of information systems and transparency in the management of Masjid At Taqwa Krandon Kudus by developing a website using the Wordpress Content Management System (CMS). The primary issues were inefficient information management and limited financial transparency. The methods used included field observations, data collection on the mosque's profile, website development, and evaluation through feedback from the mosque management and congregation. The results of this project include the creation of a mosque website that facilitates more structured and transparent information management, particularly in financial matters. The evaluation showed that the website successfully improved information accessibility for the congregation and increased trust in the mosque's management. It also provided a strong foundation for sustainable, digitally-based management in the future.